A Framework for Life–Cycle Cost Analysis for Future‐Proof Systems. Issue 1 (13th September 2016) - Rehman, Obaid Ur; Ryan, Michael
Abstract: In addition to elements that meet current capability, future‐proof system generally comprises elements to meet some or all of predicted future capability future proof system generally consists of the future capability elements (known as a projection of future capability) in the system design. The inclusion of the future projection affects the original system dynamics and thus affects the system capability and cost. The dynamics of future proofing plays an important role in the system design process and life‐cycle cost analysis (LCCA). In this paper, we present a framework for dynamic analysis of the life‐cycle cost analysis for future‐proof systems. The method presented in this paper may also be used to select an optimum future capability projection where the objective is the minimum cost of the ownership of the system. Here dynamics of future proofing is discussed in the context of the life‐cycle cost of a system. Finally, several examples are presented to explain the application of the developed framework.